PENGARUH LUAS LAHAN, MODAL DAN TENAGA KERJA TERHADAP PRODUKSI USAHATANI NANAS (Studi Kasus: Desa Bulud Kecamatan Passi Barat Kabupaten Bolaang Mongondow) - Nia Martika Mokodompit; Jane Sulinda Tambas; Jelly Ribka Danaly Lumingkewas (Sam Ratulangi University, 2021)
This study aims to determine the effect of land area, capital and labor on pineapple farming production as seen from the results of the pre-survey and farmer's share in Bulud Village. The research was carried out in Bulud Village, Passi Barat District, Bolaang Mongondow Regency from November 2020 to August 2021. The data collection method used the